Pemusnahan Uang Rupiah dalam Upacara Pitra Yadnya di Bali Perspektif Undang-Undang Nomer 7 Tahun 2011 - I Made Agus Mertajaya; I Made Suwitra; I Ketut Sukadana (Warmadewa Press, 2020)
This study aims to determine the application of sanctions to the perpetrators of the crime of destroying money in the pitra yadnya ceremony. The phenomenon that is happening now is that many Hindu people in Bali burn rupiah currency in the pitra yadnya ceremony on the grounds that it is a provision for the person being ceremonied. Grounded by the phenomenon the stuy examines two issues: a) how is regulate the destruction of money regulating in the to law Law Number 7 of 2011 concerning Currency, b) whether or not the burning of money as a fundametal provision in the pitra yadnya ceremony is classified as a criminal act. In conducting this research, the authors use normative the research method and statutory approachs and conceptual approach. Furthermore, the legal materials that have been collected are processed using the descriptive analysis method. The results showed that the regulation on the destruction of rupiah currency contained in Article 1 paragraph (10) of Law Number 7 of 2011 and Article 11 paragraph (1) to Article 11 paragraph (4) also regulates the destruction of rupiah. Burning money as a provision in the pitra yadnya ceremony cannot be classified as a criminal act because it does not fulfill the criminal element, namely the element of the intent of the act being committed and the inner will of the person burning the money in question. Apart from that, this also gets the penalties written off because they are considered connected to the public interest.